Europe's lost frontiers. - Gaffney, Vincent L.; Fitch, Simon (Archaeopress Archaeology, 2022)
'Europe's Lost Frontiers' was the largest directed archaeological research project in Europe, investigating the inundated landscapes of the Early Holocene North Sea - often referred to as 'Doggerland'. The first in a series of monographs presenting the results of the project, this book provides the context of the study and method statements.